A Review on Current Nanofiber Technologies: Electrospinning, Centrifugal Spinning, and Electro‐Centrifugal Spinning. Issue 3 (26th October 2022) - Xu, Huaizhong; Yagi, Shinichi; Ashour, Sherry; Du, Lei; Hoque, Md Enamul; Tan, Lin
Abstract: Nanofiber‐based products are widely used in the fields of public health, air/water filtration, energy storage, etc. The demand for nonwoven products is rapidly increasing especially after COVID‐19 pandemic. Electrospinning is the most popular technology to produce nanofiber‐based products from various kinds of materials in bench and commercial scales. While centrifugal spinning and electro‐centrifugal spinning are considered to be the other two well‐known technologies to fabricate nanofibers. However, their developments are restricted mainly due to the unnormalized spinning devices and spinning principles. High solution concentration and high production efficiency are the two main strengths of centrifugal spinning, but beaded fibers can be formed easily due to air perturbation or device vibration. Electro‐centrifugal spinning is formed by introducing a high voltage electrostatic field into the centrifugal spinning system, which suppresses the formation of beaded fibers and results in producing elegant nanofibers. It is believed that electrospinning can be replaced by electro‐centrifugal spinning in some specific application areas. This article gives an overview on the existing devices and the crucial processing parameters of these nanofiber technologies, also constructive suggestions are proposed to facilitate the development of centrifugal and electro‐centrifugal spinning. Abstract : This review article forces on discussing the differences and relationships of three nanofiber technologies—electrospinning, centrifugal spinning, and electro‐centrifugal spinning. It mainly summarizes the existing devices and crucial processing parameters. The electro‐centrifugal spinning combines the strengths of electrospinning and centrifugal spinning, showing potentials in processing elegant nanofibers in large scale.